Electrochemotherapy in the treatment of cutaneous malignancy: Outcomes and subgroup analysis from the cumulative results from the pan-European International Network for Sharing Practice in Electrochemotherapy database for 2482 lesions in 987 patients (2008–2019). (October 2020) - Clover, A.J.P.; de Terlizzi, F.; Bertino, G.; Curatolo, P.; Odili, J.; Campana, L.G.; Kunte, C.; Muir, T.; Brizio, M.; Sersa, G.; Pritchard Jones, R.; Moir, G.; et al.
Abstract: Background: Electrochemotherapy (ECT) is a treatment for both primary and secondary cutaneous tumours. The international Network for sharing practices on ECT group investigates treatment outcomes after ECT using a common database with defined parameters. Methods: Twenty-eight centres across Europe prospectively uploaded data over an 11-year period. Response rates were investigated in relation to primary diagnosis, tumour size, choice of electrode type, route of bleomycin administration, electrical parameters recorded and previous irradiation in the treated field. Results: Nine hundred eighty-seven patients, with 2482 tumour lesions were included in analysis. The overall response (OR) rate was 85% (complete response [CR]: 70%, partial response rate: 15%, stable disease: 11%, and progressive disease: 2%). For different histologies, OR and CR rates for metastases of malignant melanoma were 82% and 64%, basal cell carcinoma were 96% and 85%, breast cancer metastases were 77% and 62%, squamous cell carcinoma were 80% and 63% as well as Kaposi's sarcoma were 98% and 91%, respectively. Variance was demonstrated across histotypes (p < 0.0001) and in accordance with size of lesion treated (dichotomised at diameter of 3 cm (p < 0.0001). Hexagonal electrodes were generally used for larger tumours, but for tumours up to 3 cm, linear array electrodes provided better tumour control than hexagonal electrodes (80%:74%, p < 0.003). For tumours more than 2 cm, intravenous administration was superior to intratumoural (IT) administration (p < 0.05). Current recorded varied across tumour histologies and size but did not influence response rate. In previously irradiated areas, responses were selectively lower for IT administration. Conclusions: These cumulative data endorse efficiency of ECT across a broad range of histotypes. Analysis of 2482 lesions details subgroup analysis on treatment response informing future treatment choices. Highlights: Electrochemotherapy (ECT) is highly efficient in the treatment of cutaneous metastases. ECT is efficient across tumour histologies. ECT response is higher for smaller tumours. Intravenous bleomycin was more efficient than intratumoural, in tumours more than 2 cm size. Linear array electrodes were more efficient in tumours less than 3 cm size.